Usage of Social Media Marketing on the Performance assessment of SMES in Uganda: A Case Study of Kabale Municipality - Charity, Kiconco (Kabale University, 2023)
The study looked into the impact of social media marketing on the performance of SMEs in Uganda, using Kabale as a case study.The objectives of the study were to examine the impact of compatibility of social media platforms on the performance of SMEs, assess the effect of perceived usefulness of social media platforms on the performance of SMEs, and determine the effect of perceived ease of use of social media platforms on the performance of SMEs. The study employed a descriptive study design. The study population of 2,600 respondents was used, and a sample size of 335 was used. Data was collected using questionnaires and interview methods. The study's findings on the impact of social media platform compatibility on the performance of SMEs and respondents were based on an increase in brand awareness, an increase in customer relationships, a high purchasing power decision, reaching a broader range of customers, and an increased demand for the customers' needs. The study findings on the effect of perceived usefulness of social media platforms on the performance of SMEs obtained responses on how social media influences buying decisions, increases the engagement of business owners with customers, influences electronic commerce, and leads to easy modifications in marketing processes. In the findings on the effect of perceived ease of use of social media platforms on the performance of SMEs, responses were obtained that social media leads to better understanding of customer needs, easy and timely interactions with customers, quick brand modification, low operating costs in marketing processes, and convenient and easy to reach business customers. The study recommended that there should be massive branding of business products so that the awareness of the existing market products can be well known to the potential customers who can increase their purchasing power, hence business performance; business owners should try and ensure that there is a strong relationship between them and their customers so that customers can feel comfortable when buying from them, which can lead to better business performance; and due to the availability of social media platforms, business owners should ensure proper use of them so that customers from different areas can be reached in order to provide them with better services, which can lead to improved business performance